Analysis of the Effect of Inflation and Regional Minimum Wage on the Total Poor Population of North Sumatra the Period of 2001-2021 - Leonardo Siahaan; Erli Dayinati; Ulfah Nabilah Azizah Manurung (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
Poverty in the community at the national and regional levels is a complex social problem and requires an appropriate and sustainable strategy to overcome it. In North Sumatra, the number of poor people can be influenced by various factors, both economic and non-economic. The purpose of this research is to analyze the effect of inflation and minimum wages on the number of poor people in North Sumatra from 2001 to 2021 simultaneously and partially. The type of data used in this study is secondary time series data from the official website of the Central Bureau of Statistics (BPS) of North Sumatra. The analytical method used is multiple linear regression using the Eviews 10 econometric software. The results of the study partially prove that the Regional Minimum Wage has a negative and significant effect on the number of poor people in North Sumatra from 2001 to 2021 with a probability value of 0.000005. Simultaneously, the Inflation and Regional Minimum Wage variables have a significant influence on the number of poor people in North Sumatra in the same period. The R test shows that 74.0850% of the variability can be explained by these two factors, while the rest is influenced by other factors not examined in this study.